PERHITUNGAN VALUE AT RISK DENGAN PENDEKATAN VARIANCE-COVARIANCE - Berry, Yunike (JURISMA : Jurnal Riset Bisnis & Manajemen, 2017)
This study explain the calculation of market risk of VaR (in this case is the risk of equity. The data used in this study are the dominating shares in the telecommunication sector of Indonesia Stock Exchange. Research is obtained from the reference source and use secondary data. The observation period is done during three years with daily period. The research methodology used to measure the biggest potential risk (loss) caused by investing in telecommunication stock index is Value at Risk (VaR) approach using Variance-Covariance Method Based on the result of research, ISAT has a higher level of volatility compared to others, thus indicating a higher market risk. Keyword: Value at Risk (VaR), Variance-covariance, Telecommunication Sector